PENGARUH PELATIHAN KERJA DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PT ISS INDONESIA SUB SECURITY SERVICE UOB PLAZA - Fitri Qori'ah; Shela Indah Savitri (Al Hasanah Barokah Foundation, 2026)
This study aims to determine the effect of Job Training and Career Development on Employee Performance at PT ISS Indonesia Sub Security Service UOB Plaza. The research method used is quantitative. The population consists of 250 employees, and the sampling technique was determined using the Slovin formula, resulting in a sample of 71 respondents. The analysis methods employed include validity test, reliability test, classical assumption test, simple and multiple linear regression analysis, correlation coefficient test, coefficient of determination test, t-test, and F-test with the assistance of the Statistical Package for Social Science (SPSS) software.The results of the study show that, partially, job training has a positive and significant effect on employee performance, with a t-value of 6.125 and a significance value of 0.000, which is smaller than the 0.05 significance level. Career development also has a positive and significant effect, with a t-value of 5.905 and a significance value of 0.000, which is smaller than 0.05. Job Training (X1) and Career Development (X2) simultaneously have a positive and significant effect on Employee Performance (Y). This is evidenced by the F-value of 82.881 with a significance value of 0.000, which is smaller than 0.05. Based on the multiple linear regression analysis, the equation is Y = 12.502 + 0.472X₁ + 0.444X₂, with a coefficient of determination showing that the contribution effect is 70.9%, while the remaining 29.1% is influenced by other factors not examined in this study.